Scanning speed phenomenon in contact-resonance atomic force microscopy - Glover, Christopher C.; Killgore, Jason P.; Tung, Ryan C. (Beilstein Journal of Nanotechnology, 2018)
This work presents data confirming the existence of a scan speed related phenomenon in contact-mode atomic force microscopy (AFM). Specifically, contact-resonance spectroscopy is used to interrogate this phenomenon. Above a critical scan speed, a monotonic decrease in the recorded contact-resonance frequency is observed with increasing scan speed. Proper characterization and understanding of this phenomenon is necessary to conduct accurate quantitative imaging using contact-resonance AFM, and other contact-mode AFM techniques, at higher scan speeds. A squeeze film hydrodynamic theory is proposed to explain this phenomenon, and model predictions are compared against the experimental data.
Keywords: atomic force microscope; contact resonance; liquid; phenomenon; scan speed